You are here:

**Please provide a rating**, it takes seconds and helps us to keep this resource free for all to use

This Arithmetic Progression Calculator is one of two specialist calculators designed to calculate arithmetic progression based on specific known criterea. The Arithmetic Progression First Term Calculator will calculate:

- The sum of the first n-terms of an arithmetic series when the first term and the common difference are given.

You can also calculate the sum of the first n-terms of an arithmetic series when any two terms of the series are given using this Arithmetic Progression Calculator

**Arithmetic Progression First Term Calculator Parameters:** The number of terms is a natural (counting) number.

Sum of the first n-terms (S_{n}) = |

Arithmetic Progression Calculations and Formula |
---|

S_{n} = [2 ∙ x_{1} + (n - 1) ∙ d] ∙ n/2S _{n} = [2 ∙ + ( - 1) ∙ ] ∙ /2S _{n} = [2 ∙ + ∙ ] ∙ /2S _{n} = ∙ /2S _{n} = /2S _{n} = |

Arithmetic Progression First Term Calculator Input Values |

First term of the arithmetic progression (x_{1}) = |

Common difference (d) = |

Total number of terms (n) = |

Please note that the formula for each calculation along with detailed calculations is shown further below this page. As you enter the specific factors of each arithmetic progression first term calculation, the Arithmetic Progression First Term Calculator will automatically calculate the results and update the formula elements with each element of the arithmetic progression first term calculation. You can then email or print this arithmetic progression first term calculation as required for later use.

We hope you found the Arithmetic Progression First Term Calculator useful, if you did, we kindly request that you rate this calculator and, if you have time, share to your favourite social network. This allows us to allocate future resource and keep these Math calculators and educational material free for all to use across the globe.

**Please provide a rating**, it takes seconds and helps us to keep this resource free for all to use

The Arithmetic Progression First Term Calculator has practical application and use in the following fields and disciplines

An arithmetic progression is a special type of number sequence where the difference between any two consecutive terms is always constant. This common difference is denoted by d, while the terms of the arithmetic progression are denoted by x_{1}, x_{2}, x_{3}, , x_{n} (or a_{1}, a_{2}, a_{3}, , a_{n}), where x_{1} (or a_{1}) is the first term, x_{2} (or a_{2}) the second term, and so on. The n-term x_{n} (or a_{n}) is known as the general term of the arithmetic progression.

For example, 4, 7, 10, 13, is an arithmetic progression where the first term is x_{1} = 4, the second term is x_{2} = 7, and so on. The common difference d is obtained by subtracting two consecutive terms, for example, x_{2} - x_{1}, where in this specific case, we have d = 7 - 4 = 3.

In general, we have

x_{2} = x_{1} + d

x_{3} = x_{2} + d = x_{1} + 2d

x_{4} = x_{3} + d = x_{1} + 3d

⋮

x_{n} = x_{n - 1} + d = x_{1} + (n - 1) ∙ d

x

x

⋮

x

The last row gives the general formula for the n-th term of an arithmetic progression. It is

x_{n} = x_{1} + (n - 1) ∙ d

Another thing we can do with an arithmetic progression is to find the sum of the first n-terms. For this, we use a formula known as the Gauss Law. We can derive this formula by taking the sum of the first n-terms of an arithmetic progression in two ways: (1) in terms of x_{1}, i.e. from the first to the last, and (2) in terms of x_{n}, i.e. from the last to the first. We have

S_{n} = x_{1} + x_{2} + x_{3} + ⋯ + x_{n}

and

S_{n} = x_{n} + x_{n - 1} + x_{n - 2} + ⋯ + x_{1}

Writing everything in terms of x_{1} in the first formula and in terms of x_{n} in the second formula yields

S_{n} = x_{1} + (x_{1} + d) + (x_{1} + 2d) + ⋯ + [x_{1} + (n - 1)d]

and

S_{n} = x_{n} + (x_{n} - d) + (x_{n} - 2d) + ⋯ + [x_{n} - (n - 1)d]

Adding the two formulas brings the cancelling out of all d-related terms. In this way, we obtain

S_{n} + S_{n} = __(x___{1} + x_{n} ) + (x_{1} + x_{n} ) + ⋯(x_{1} + x_{n} )__︸____n times__

We can write this formula in a shorter way as

2S_{n} = (x_{1} + x_{n} ) ∙ n

or

S_{n} = *(x*_{1} + x_{n} ) ∙ n*/**2*

The last formula is the mathematical representation of the Gauss Law. It allows us to calculate the sum of the first n-terms of an arithmetic progression when the first term and the common difference are known.

For example, if we want to calculate the sum of the first 50 terms (n = 50) of the arithmetic progression 6, 13, 20, (x_{1} = 6 and d = x_{2} - x_{1} = 13 - 6 = 7), first we find the 50th term (x_{50}) using the formula

x_{n} = x_{1} + (n - 1) ∙ d

Then, we calculate the sum of the first 50 terms of this progression through the Gauss formula

S_{n} = *(x*_{1} + x_{n} ) ∙ n*/**2*

Thus, we have

x_{50} = 6 + (50 - 1) ∙ 7

= 6 + 49 ∙ 7

= 6 + 343

= 349

= 6 + 49 ∙ 7

= 6 + 343

= 349

and

S_{50} = *(6 + 349) ∙ 50**/**2*

= 8875

= 8875

It is clear that any attempt to calculate the sum of these terms one by one would require a lot of time and efforts.

If the first term is unknown but we know two other terms x_{p} and x_{q} of the sequence, where p and p show the number of the corresponding term, first we calculate the common difference using the formula

d = *x*_{q} - x_{p}*/**q - p*

then, we use the approach explained earlier to find whatever else is required. For example, if in an arithmetic progression are given only x_{8} = 23 and x_{14} = 35 (p = 8 and q = 14) and the sum of the first 30 terms is required (n = 30), first we calculate the common difference d through the formula

d = *x*_{q} - x_{p}*/**q - p*

=*x*_{14} - x_{8}*/**14 - 8*

=*35 - 23**/**14 - 8*

=*12**/**6*

= 2

=

=

=

= 2

Next, we calculate the first term given that x_{8} = 23 and d = 2 are already known. Thus, for n = 8, we obtain

x_{n} = x_{1} + (n - 1) ∙ d

x_{1} = x_{n} - (n - 1) ∙ d

= 23 - (8 - 1) ∙ 2

= 23 - 7 ∙ 2

= 23 - 14

= 9

x

= 23 - (8 - 1) ∙ 2

= 23 - 7 ∙ 2

= 23 - 14

= 9

The next step involves finding the 30th term (n = 30). We use the same formula as above to find it. Thus,

x_{n} = x_{1} + (n - 1) ∙ d

x_{30} = x_{1} + (30 - 1) ∙ d

x_{30} = 9 + (30 - 1) ∙ 2

= 9 + 29 ∙ 2

= 9 + 58

= 67

x

x

= 9 + 29 ∙ 2

= 9 + 58

= 67

Last, we calculate the sum of the first 30 terms (n = 30) for which the question is interested. We use the Gauss Law formula for this purpose. Thus,

S_{n} = *(x*_{1} + x_{n}) ∙ n*/**2*

S_{n} = *(9 + 67) ∙ 30**/**2*

=*76 ∙ 30**/**2*

= 1140

S

=

= 1140

All the above reasoning can be extended to include other numbers as well, not just integers. Only the number of terms n must be a natural number.

The following Math tutorials are provided within the Sequences and Series section of our Free Math Tutorials. Each Sequences and Series tutorial includes detailed Sequences and Series formula and example of how to calculate and resolve specific Sequences and Series questions and problems. At the end of each Sequences and Series tutorial you will find Sequences and Series revision questions with a hidden answer that reveal when clicked. This allows you to learn about Sequences and Series and test your knowledge of Math by answering the revision questions on Sequences and Series.